A formação matemática do pedagogo: a relação entre o raciocínio matemático e as estratégias na solução de problemas matemáticos - Bezerra, Antonio Marcelo Araújo (2017)
The initial training in the Pedagogy Course of the Faculty of Education (FACED) of the Federal University of Ceará (UFC) involves an understanding by the student (future-teacher) not only of contents to be worked with his students, but also pedagogical practices that better facilitate the didactic transposition of knowledge. Faced with a teaching that is sometimes filled with rules to be memorized and with no meaning for the student, in particular the mathematical contents, we aim to analyze how mathematical strategies presented by the students of the Pedagogy course, aiming at a classification of mathematical problems not referring to reasoning : (i) concrete; (ii) graph (iii) arithmetic; and (iv) algebraic, with a view to the construction and not only the memorization of facts and formulas, raising questions related to the formation of the mathematics teacher. This research of a qualitative nature occurred in part with: (a) observation of mathematics classes; and (b) accomplishment of a set of mathematical problems, activities with the unemployed during a course of mathematics teaching in the course of the Course of Pedagogy semester of 2016.1. Previously, we also searched in books, theses and periodicals, research on teaching and learning math in the early years of elementary school. Collected as information, we began as analyzes on how strategies for students in solving the problems categorized as answers from the series made by Johannot (1947) regarding mathematical reasoning. The results indicate new and better spaces for reflection both in initial teacher training and in updating with students of Basic Education, especially in the initial years of elementary education. We show with this research the relevance in terms of an understanding of how Pedagogy students build their problem solving strategies and as consequences for the teaching of mathematical contents. What is the object of study of the research and the understanding of the strategies presented by the students on the mathematical reasoning, for the understanding as the strong support as observations to the actions mediated by the teacher, in particular, in the construction of new knowledge through the Fedathi Sequence.